2011
DOI: 10.1002/ppul.21567
|View full text |Cite
|
Sign up to set email alerts
|

Bronchodilator responsiveness in wheezy infants and toddlers is not associated with asthma risk factors

Abstract: Background There are limited data assessing bronchodilator responsiveness (BDR) in infants and toddlers with recurrent wheezing, and factors associated with a positive response. Objectives In a multicenter study of children ≤ 36 months old we assessed the prevalence of and factors associated with BDR among infants/toddlers with recurrent episodes of wheezing. Methods Forced expiratory flows and volumes using the raised-volume rapid thoracic compression method were measured in 76 infants/toddlers (mean (sd)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 34 publications
2
12
0
1
Order By: Relevance
“…Our findings of boys with airway obstruction compared with girls are consistent with prior reports (27,(34)(35)(36), and the finding of black infants with increased airway obstruction compared with white infants also supports previous studies (37)(38)(39). The responsiveness to bronchodilators in our study (29% of infants) is comparable to that reported by Goldstein and colleagues (40), who found response to albuterol in 20 to 25% of a small cohort of healthy infants and young children born at more than 36 weeks of age, and to those of Debley and colleagues, who reported a bronchodilator response in 24% of 76 infants with recurrent wheezing (41). Bronchodilator response in infants with bronchopulmonary dysplasia is reported to be slightly higher at 35% (42).…”
Section: Original Researchsupporting
confidence: 81%
“…Our findings of boys with airway obstruction compared with girls are consistent with prior reports (27,(34)(35)(36), and the finding of black infants with increased airway obstruction compared with white infants also supports previous studies (37)(38)(39). The responsiveness to bronchodilators in our study (29% of infants) is comparable to that reported by Goldstein and colleagues (40), who found response to albuterol in 20 to 25% of a small cohort of healthy infants and young children born at more than 36 weeks of age, and to those of Debley and colleagues, who reported a bronchodilator response in 24% of 76 infants with recurrent wheezing (41). Bronchodilator response in infants with bronchopulmonary dysplasia is reported to be slightly higher at 35% (42).…”
Section: Original Researchsupporting
confidence: 81%
“…The thresholds for a positive bronchodilator response in our study (Table 4) were similar to those obtained in other studies that included younger children. 24,25 In a recent publication, designed to assess the reproducibility and repeatability of spirometry in preschool children, thresholds were 14% for FEV 0.75 and 33% for FEF 25---75 , because coefficients of repeatability were higher than that in our study. 26 That could be explained because in the Borrego study they included a placebo inhaler, which may explain the greater variability and consequently an increase in the cut-off points for considering a significant response to bronchodilator.…”
Section: Variablementioning
confidence: 67%
“…In older infants, increased bronchial tone can be present prior to any wheeze episodes, 72 but bronchodilator response of infants with history of wheeze has been inconsistently associated with asthma risk. 73,74 …”
Section: Workgroup 4: Pulmonary Development (Group Membership: Table 1)mentioning
confidence: 99%